STUDY FISHING GROUND IN KAMPAR KIRI RIVER GUNUNG SAHILAN VILLAGE, GUNUNG SAHILAN DISTRICT, KAMPAR REGENCY, PROVINCE OF RIAU - Siti Maryam; Alit Hindri Yani; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in May 2015 during the dry season in Kampar Kiri river Gunung Sahilan village, Gunung Sahilan district, Kampar regency, province of Riau. Purpose of this study was to obtain data on environmental parameters become the benchmark fishing grounds and fishing activity. Environmental parameters measured are temperature, current speed, brightness, depth, acidity (pH) and dissolved oxygen. After doing this research is that the condition of the Kampar Kiri river Gunung Sahilan village still quite good and still support for life of organisms that were in it and deserves to fishing activities in these waters.Keyword : fishing ground, environmental parameters, kampar kiri river